DOMINANTS AND MECHANISMS OF OVERCOMING ENVIRONMENTAL RISKS TO ENSURE SUSTAINABLE DEVELOPMENT - Garashchuk, O. V.; Kutsenko, V. I. (Scientific Progress & Innovations, 2021)
Sustainable development is the leading conceptual idea, which, according to the generally accepted opin-ion of the world scientific community, has to determine the direction of modern civilization. Its essence is to meet social needs for material benefits without threatening the ability of future generations to satisfy their own needs. Sustainable development includes environmental, economic and social components. Moreover, it is especially important to ensure environmental security, identify factors affecting the overcoming of envi-ronmental risks. Therefore, the purpose of our study is to identify mechanisms, the successful implementation of which would contribute to improving the environmental situation and ensuring sustainable development. Environmental security, as a part of national security, occupies an important place among its components. Environmental problems are aggravated in the process of transition to market relations. Sustainable devel-opment requires an optimal combination of market mechanisms and measures of state regulation of social and economic development, aimed at creating ecologically safe environment for human living. Such envi-ronment significantly increases the role of the social sphere and, in particular, housing and communal ser-vices, the functioning of which negatively affects the environment as a result of depreciated sewer systems and insufficient capacity of purification facilities. The article provides a list of measures aimed at overcom-ing this negative situation. The role of education, which can have a significant impact on the ecological state in the country, is also emphasized. Education can be called a dominant factor in achieving sustainable de-velopment. A number of measures aimed at enhancing the role of environmental education in the life of the society are proposed, in particular to achieving environmental security, overcoming environmental risks, and increasing production efficiency based on sustainable development. The idea is substantiated as to in-troducing an innovative mechanism aimed at improving the natural environment, which will contribute to successful overcoming of environmental problems and dynamic movement to sustainable development.